2022
DOI: 10.1149/1945-7111/ac50de
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Activity Enhancement Using Graphene-Metal Oxide Nanocomposites for the Ultra Low Level Detection of Biomolecules

Abstract: Metal oxide reduced graphene oxide (MO/RGO, MO = NiO, Co3O4 and SnO2) nanocomposites were synthesized by cost-effective hydrothermal method. The structural, thermal, and morphological characteristics of composites were investigated using PXRD, FT-IR, TGA, Raman, SEM and HR-TEM. Modified carbon paste electrochemical sensors based on NiO/RGO, Co3O4/RGO and SnO2/RGO were developed and compared for the effective detection of Epinephrine (EPN), Serotonin (SER) and Tyrosine (TYR). The performance of the NiO/RGO/CPE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Two-dimensional materials like graphene, 12−14 TMDs, 15 or LDHs 16 have become the most promising candidates for enzyme-like catalysis thanks to their unique physical and chemical properties (ultrathinness, large specific surface area, and electronic mobility in two-dimensional space 17 AA or biochemical components include cobalt oxyhydroxide nanoflakes, 18 graphene, 19 and MoTe 2 , 20 but they are not sensitive enough, and they take too long to detect AA. The S defect-rich ultrathin 2D MoS 2 21 made in our laboratory was used to produce a blue product (ox TMB) by enzyme-like catalytic oxidation of TMB in the presence of H 2 O 2 .…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two-dimensional materials like graphene, 12−14 TMDs, 15 or LDHs 16 have become the most promising candidates for enzyme-like catalysis thanks to their unique physical and chemical properties (ultrathinness, large specific surface area, and electronic mobility in two-dimensional space 17 AA or biochemical components include cobalt oxyhydroxide nanoflakes, 18 graphene, 19 and MoTe 2 , 20 but they are not sensitive enough, and they take too long to detect AA. The S defect-rich ultrathin 2D MoS 2 21 made in our laboratory was used to produce a blue product (ox TMB) by enzyme-like catalytic oxidation of TMB in the presence of H 2 O 2 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Two-dimensional materials like graphene, TMDs, or LDHs have become the most promising candidates for enzyme-like catalysis thanks to their unique physical and chemical properties (ultrathinness, large specific surface area, and electronic mobility in two-dimensional space), which have attracted wide interest among researchers. Examples of 2D materials that have already been used for the detection of AA or biochemical components include cobalt oxyhydroxide nanoflakes, graphene, and MoTe 2 , but they are not sensitive enough, and they take too long to detect AA.…”
Section: Introductionmentioning
confidence: 99%
“…While, the analytical performance of MIES is frequently limited by the properties of the electrode surface modification materials, and the use of nanomaterials with excellent electrical conductivity for modifying the electrodes has become an effective way to solve the above problems. 24,25 Graphene oxide (GO) is a popular material with unique characteristics such as high surface area and considerable charge carrier conductance. Many studies have shown that GO combined with other materials exhibits excellent electrochemical properties.…”
mentioning
confidence: 99%